Optimizing Japanese Entrepreneurship for Startup Growth and Sustainability in ASEAN Lower-Middle-Income Economies - Hara, Masatoshi (International Journal of Industrial Engineering and Management, 2026)
This study investigates how Japanese entrepreneurship contributes to the strengthening of startup ecosystems in lower-middle-income ASEAN economies. Even with the dynamic expansion of these economies, they continue to grapple with historic challenges such as the Middle-Income Trap, institutional weaknesses, and limited access to capital. Japanese firms contribute to the enhancement of the scalability and competitiveness of ASEAN startups by implementing production management strategies—including lean concepts, digitalization, and cross-cultural collaboration. Through a qualitative examination of Japanese-ASEAN partnerships, the study identifies key success factors as technology transfer, structured business processes, and adaptation to markets. While Japanese investment and management expertise increase the effectiveness of operations, cultural disparities and regulatory mismatches remain significant obstacles to seamless collaboration. To address the challenges, the study proposes integrative solutions for conciliating Japanese models of production with ASEAN business culture with a view to enabling sustainable entrepreneurial growth. Applying the Grounded Theory Method, the research adds theory to international entrepreneurship and production management literature while also offering practitioner implications. By optimizing Japanese investment trends and institutional alignment, the study offers policymakers, investors, and entrepreneurs’ actionable recommendations to strengthen ASEAN startup ecosystems. Enhancing Japanese-ASEAN economic collaboration is imperative to foster innovation and long-term economic development in the region. Article history: Received (February 27, 2025); Revised (November 29, 2025); Accepted (December 12, 2025); Published online (February 18, 2026)